Base-mediated intramolecular C- and N-arylation of N,N-disubstituted 2-nitrobenzenesulfonamides: advanced intermediates for the synthesis of diverse nitrogenous heterocycles - Smyslová, Petra; Kisseljova, Ksenija; Krchňák, Viktor (ACS combinatorial science, 2014)
Structural and electronic features that facilitate and direct the intramolecular C- and N-arylation of 2-alkyl-2-{[N-(benzyl)-2-nitrophenyl]sulfonamido}acetic acid esters and amides were examined. The substitution pattern and amino acid carboxy-terminal functionality determined the arylation position. C/N-arylated products represent advanced intermediates for combinatorial synthesis of diverse nitrogenous heterocycles, including indazoles, quinazolinones, quinoxalinones, and 3-amino-2-oxindoles.
Keywords: arylation; diversity-oriented synthesis; Molecular Structure; nitrobenzenesulfonamides; Nitro Compounds; molekulární struktura; Sulfonamides; Heterocyclic Compounds; Carbon; uhlík; C−C bond formation; sulfonamidy; Nitrogen; heterocycle; dusík; dusíkaté sloučeniny; heterocyklické sloučeniny